1998
DOI: 10.2500/105065898780707991
|View full text |Cite
|
Sign up to set email alerts
|

Tri-Nasal Triamcinolone Acetonide Nasal Spray 200 and 400 μg qd versus Placebo and Nasacort Triamcinolone Acetonide Nasal Aerosol 440 μg qd in Patients Suffering from Seasonal Allergic Rhinitis during the Grass Season

Abstract: Tri-Nasal Nasal Spray is an investigational solution of triamcinolone acetonide (TAA) currently being evaluated as a treatment for allergic rhinitis. The safety and efficacy of 200 and 400 micrograms once daily doses of Tri-Nasal Nasal Spray, an active control (440 micrograms once daily of Nasacort Nasal aerosol), and Tri-Nasal Nasal Spray placebo were compared over a 2-week treatment period in a double-blind (the Nasacort treatment was not blinded), parallel design trial. A total of 377 adult patients in 13 c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2001
2001
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 7 publications
0
3
0
Order By: Relevance
“…A major limitation of these meta-analyses was the number of trials ineligible for inclusion because of insuffici t TNSS reporting. To be eligible for the meta-analyses, the TNSS had to be reported in such a way that actual scores at the end of the primary assessment period could be directly controls (46,47) . The average baseline TNSS scores in the combination treatment were approximately 1.5 points (out of max of 12) higher than the average baseline in the INCS trials.…”
Section: Discussionmentioning
confidence: 99%
“…A major limitation of these meta-analyses was the number of trials ineligible for inclusion because of insuffici t TNSS reporting. To be eligible for the meta-analyses, the TNSS had to be reported in such a way that actual scores at the end of the primary assessment period could be directly controls (46,47) . The average baseline TNSS scores in the combination treatment were approximately 1.5 points (out of max of 12) higher than the average baseline in the INCS trials.…”
Section: Discussionmentioning
confidence: 99%
“…Ebastine (16, 17, 25), which is now available in Europe, has been shown to be at least as effective as cetirizine (25) and superior in efficacy to loratadine (26). Triamcinolone acetonide nasal spray (17–19, 27) is used worldwide and has been found to have an efficacy similar to other topical corticosteroids in the treatment of seasonal allergic rhinitis (28). Nedocromil sodium is widely used in Europe for the topical treatment of allergic conjunctivitis and has been shown to be at least as effective as sodium cromoglycate (29) and levocabastine (30) ophthalmic solutions.…”
Section: Discussionmentioning
confidence: 99%
“…100 Mometasone furoate was effective in relieving congestion across all severities of seasonal allergic rhinitis, with the magnitude of the benefit greatest in patients with the most severe congestion (Figure 4). 100 A 2-week study of adults with seasonal allergic rhinitis reported that once-daily treatment with triamcinolone acetonide significantly reduced nasal symptoms, including congestion,101 and a 2-week study including adults and adolescents with seasonal allergic rhinitis reported that once-daily treatment with fluticasone furoate significantly reduced nasal symptoms, including congestion 102. In a 2-week study of adults and adolescents with seasonal allergic rhinitis, once-daily treatment with ciclesonide significantly reduced total nasal symptoms.…”
Section: Pharmacologic Therapy For Congestionmentioning
confidence: 99%